If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + 5 + -9) = 0 Reorder the terms: 3(5 + -9 + x) = 0 Combine like terms: 5 + -9 = -4 3(-4 + x) = 0 (-4 * 3 + x * 3) = 0 (-12 + 3x) = 0 Solving -12 + 3x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 3x = 0 + 12 Combine like terms: -12 + 12 = 0 0 + 3x = 0 + 12 3x = 0 + 12 Combine like terms: 0 + 12 = 12 3x = 12 Divide each side by '3'. x = 4 Simplifying x = 4
| 103+5x=8x+170 | | 5c^2+15c+18=2c^2 | | 3(2x-y)=108forx | | x^2-48x+540=0 | | (x/3)-2=2x-17 | | -35+9x=9+7x | | 3x-0y=27 | | 3x-2y-40=x+3y+20 | | -5d=6/-6 | | 4d+8=6d-4 | | lx-2l=x/3 | | 7(5x+8)=12-x-4 | | 5b-2c^2=3(b-2) | | 3x^2-16x+16=720 | | 2n(3n-4)=0 | | 7x+8a=124 | | -8(5x-6)= | | f(z)=z^2-2z | | 5z*3z= | | 32=x+7+3x+x+x+7+3x+x | | -61-3x=3x+34 | | 4(3x-1)=2(2x+7) | | -2/3(6x+7)=18 | | 9b+3-4b-10=3 | | 8y=5x+17 | | 3(2x+1)=5x-4 | | 16+2n=24 | | y-1.2=4/8 | | p(x+1)(x-3)=0 | | j^2+5j=-4 | | x^2+13x=-22 | | -31=8+-6p+-7p |